Turnover Intention Ditijau dari Stres Kerja pada Karyawan - Devi, Devi; Lutfah, Dewi; Sihotang, Yeni Irawaty; Elvinawaty, Rianda (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2020)
This study aims to determine the relationship between turnover intentionwith work stress. The hypothesis of this study states that there is a positive relationship between turnover intention and work stress, assuming that the higher the work stress is, the higher the turnover intention, and conversely the lower the work stress is, the lower the turnover intention will be. The subjects of this study were 182 employees of PT. INDAKO TRADING COY MEDAN. Datas were obtained from scales used to measure turnover intention and work stress. Calculations were performed by testing the analysis requirements (assumption) that consisted of tests for normality and linearity. The data were analyzed using Product Moment Correlation with SPSS 20 for Windows. The results of the data analysis showed that the correlation coefficient was 0.405 with a significance value of 0.000 (p <0.05). It showed that there is a positive relationship between turnover intention and work stress. The results of this study indicate that the contributions made by the variable of work stress on turnover intention was 16,4 percent, while the remaining 83,6 percent was influenced by other factors that were not examined. From these results, it is concluded that the hypothesis, which stated that there is a positive relationship between the turnover intention and work stress, is acceptable.